Length of the ranch-of-origin weaning period Does not affect post-receiving growth or carcass merit of ranch-direct, early-weaned beef calves - J.W. Bolte; K. C. Olson; Todd W. Schmidt; Bradley J. White; George A. Milliken; N.A. Sproul; L.A. Pacheco; M.D. Thomas; John R. Jaeger; Daniel U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2009)
Bovine respiratory disease (BRD) is the most economically devastating feedlot disease. Risk factors associated with incidence of BRD include (1) stress associated with maternal separation, (2) stress associated with introduction to an unfamiliar environment, (3) low intake associated with introduction of novel feedstuffs into the animal's diet, (4) exposure to novel pathogens upon transport to a feeding facility and commingling with unfamiliar cattle, and (5) inappropriately administered respiratory disease vaccination programs. Management practices that are collectively referred to as preconditioning are thought to minimize damage to the carcass from the BRD complex. Preconditioning management can reduce the aforementioned risk factors for respiratory disease by (1) using a relatively long ranch-of-origin weaning period following maternal separation, (2) exposing calves to concentrate-type feedstuffs, and (3) producing heightened resistance to respiratory disease-causing organisms through a preweaning vaccination program. The effectiveness of such programs for preserving animal performance is highly touted by certain segments of the beef industry but poorly documented in peerreviewed scientific literature. Ranch-of-origin weaning periods of up to 60 days are suggested for preconditioning beef calves prior to sale; however, optimal length of the ranch-of-origin weaning period has not been determined experimentally. The objective of this study was to test the validity of beef industry assumptions about the appropriate length of ranch-of-origin weaning periods for calves aged 100 to 160 days and weaned during the summer.
Keywords: Cattlemen' s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; BRD; Beef; Cattle; Weaning